Approximation of Classes of ψ-Integrals of Periodic Functions of Many Variables by Rectangular Linear Means of Their Fourier Series - Bodraya, V. I.; Novikov, O. A.; Rukasov, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We obtain asymptotic equalities for deviations of rectangular linear means of Fourier series on classes of ψ-integrals of multivariable functions